'Dehumanized housing' and the ideology of property as a social function. (February 2020) - Davy, Benjamin
For about 250 years, private property has been ideologized as an instrument of the owners' power to exclude. The most popular expression of the ideology of exclusion (although not his exclusive invention) is attributed to Sir William Blackstone. Speculative vacancies, a recent development in the real estate industry criticized by the UN Special Rapporteur on housing, emphasize the anti-social ideology of Blackstonian property. The article suggests that an ideology proposed by the French jurist Léon Duguit should be considered as an alternative. Based on the teachings of Comte and Durkheim, Duguit rejected the idea of property as a right and treated property as a social function. His views offer spatial planners new opportunities to define the content and boundaries of private property in land.